2021
DOI: 10.1038/s41598-021-01251-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activities of plant aqueous extracts against Salmonella Typhimurium and their application to improve safety of pork meat

Abstract: Nine odorless laboratory-collected hydro-distilled aqueous extracts (basil, calendula, centrifuged oregano, corn silk, laurel, oregano, rosemary, spearmint, thyme) and one industrial steam-distilled oregano hydrolate acquired as by-products of essential oils purification were screened for their in vitro antimicrobial activity against three Salmonella Typhimurium strains (4/74, FS8, FS115) at 4 and 37 °C. Susceptibility to the extracts was mainly plant- and temperature-dependent, though strain dependent effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…"Southern Yunnan Materia Medica" records its treatment of swelling and pain [46]. Modern research shows that corn silk contains sugars, flavonoids, mineral elements, volatile oils, alkaloids, amino acids, and other chemical components that have anti-oxidant [47], antibacterial [48], antitumor [49], blood sugar-lowering [50], and other pharmacological effects. A recent study found that corn silk can reduce serum uric acid levels by 26.69% (p < 0.05) and serum xanthine oxidase (XO) activity by 11.29% (p < 0.05) [51].…”
Section: Discussionmentioning
confidence: 99%
“…"Southern Yunnan Materia Medica" records its treatment of swelling and pain [46]. Modern research shows that corn silk contains sugars, flavonoids, mineral elements, volatile oils, alkaloids, amino acids, and other chemical components that have anti-oxidant [47], antibacterial [48], antitumor [49], blood sugar-lowering [50], and other pharmacological effects. A recent study found that corn silk can reduce serum uric acid levels by 26.69% (p < 0.05) and serum xanthine oxidase (XO) activity by 11.29% (p < 0.05) [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that clinical isolates of Salmonella spp. was naturally resistant to ampicillin, chloramphenicol, and sulphamethoxazole/trimethoprim (Gong et al, 2022). However, some study demonstrated that the clinical isolates of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In attempt to overcome the multi-drug resistant Salmonella spp., natural products based on their secondary metabolites have been used as an alternative treatment against the pathogen (Naz et al, 2022). The aqueous extracts of oregano, thyme, calendula, and basil exhibited bactericidal activity against S. Typhimurium (Gavriil et al, 2021). In the present study, we focused on Piper betle L. leaf extract, known as a betel vine.…”
Section: Introductionmentioning
confidence: 99%
“…S . Typhimurium is one of the most common serovars isolated from pork (Gavriil et al, 2021). Despite the efforts undertaken to maintain good hygienic practices throughout the production of meat, complete prevention of microbial contamination has not attained yet.…”
Section: Introductionmentioning
confidence: 99%
“…S. Typhimurium outbreaks have become more common around the globe and their prevalence has been highly associated with the animal products such as eggs, pork, and poultry. S. Typhimurium is one of the most common serovars isolated from pork (Gavriil et al, 2021). Despite the efforts undertaken to maintain good hygienic practices throughout the production of meat, complete prevention of microbial contamination has not attained yet.…”
mentioning
confidence: 99%